Long‐Term Outcome of Ustekinumab Therapy for Behçet's Disease. Issue 10 (12th August 2019) - Mirouse, Adrien; Barete, Stéphane; Desbois, Anne‐Claire; Comarmond, Cloé; Sène, Damien; Domont, Fanny; Bodaghi, Bahram; Ferfar, Yasmina; Cacoub, Patrice; Saadoun, David; ,
Abstract : Objective: Oral ulcers, the hallmark lesion of Behçet's disease (BD), can be disabling and resistant to conventional treatment, and there is a need for safe and effective treatment. We undertook this study to investigate the long‐term safety and efficacy of ustekinumab therapy for BD‐related oral ulcers that are resistant to colchicine. Methods: This multicenter, prospective, open‐label study included 30 patients who fulfilled the criteria of the International Study Group for BD and who were diagnosed as having active oral ulcers resistant to colchicine. Patients were treated subcutaneously with ustekinumab 90 mg at inclusion, at week 4, and then once every 12 weeks. Each patient was assessed longitudinally for the presence and number of oral ulcers, and median numbers of oral ulcers (with interquartile range [IQR]) were calculated. The primary efficacy end point was the proportion of patients at week 12 who experienced complete response, defined as having no oral ulcers. Results: The median number of oral ulcers per patient during ustekinumab therapy was significantly lower at week 12 compared to baseline (0 [IQR 0–1] versus 2 [IQR 2–3]; P < 0.0001). Complete response was achieved in 60.0% and 88.9% of patients at weeks 12 and 24, respectively. The median Behçet's Syndrome Activity Score (in which higher scores indicate more active disease) was significantly lower at weeks 12 and 24 (17.5 [IQR 10–42.5] and 10 [IQR 8–11], respectively) versus baseline (70 [IQR 50–70]; P < 0.0001). After a median follow‐up of 12 months (IQR 6–16 months), 26 patients (86.7%) were still receiving ustekinumab treatment. Reasons for ustekinumab discontinuation included BD flare (n = 3) and side effects (n = 1). Seven patients (23.3%) experienced adverse events, including headaches (n = 4) and asthenia (n = 2), with no serious side effects. Conclusion: Ustekinumab seems to be effective in treating BD‐related oral ulcers that are resistant to treatment with colchicine.